2020
DOI: 10.5194/amt-13-4683-2020
|View full text |Cite
|
Sign up to set email alerts
|

Automated precipitation monitoring with the Thies disdrometer: biases and ways for improvement

Abstract: Abstract. The intensity and phase of precipitation at the ground surface can have important implications not only for meteorological and hydrological situations but also in terms of hazards and risks. In the field, Thies disdrometers are sometimes used to monitor the quantity and nature of precipitation with high temporal resolution and very low maintenance and thus provide valuable information for the management of meteorological and hydrological risks. Here, we evaluate the Thies disdrometer with respect to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 51 publications
3
36
1
Order By: Relevance
“…The hydrometeors-type employed have been commonly used to describe the composition of DSDs [24,27,52,56]. Indeed, by superimposing these fall velocity-diameter relationships over the measured DSDs, almost 88% of the particles matched the envelope formed between snow and rain curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrometeors-type employed have been commonly used to describe the composition of DSDs [24,27,52,56]. Indeed, by superimposing these fall velocity-diameter relationships over the measured DSDs, almost 88% of the particles matched the envelope formed between snow and rain curves.…”
Section: Discussionmentioning
confidence: 99%
“…First, the fall velocitydiameter relationship was calculated for raindrops (R), snow (S), wet snow (WS), graupel (G), lump graupel (LG), soft hail (SH), fresh hail (FH), and lump hail (LH). The relationships and diameters selected (Table 2) were based on the most common formulations for these hydrometeors found in the literature [24,[53][54][55][56]. A correction factor was applied to the fall velocity values in order to consider the velocity increase caused by the decrease in air density [57].…”
Section: Correction Of Dsd 321 Dsd Decompositionmentioning
confidence: 99%
“…7,8 The correlation between the precipitation rate and both the measured transmission signal and the data from the visibility sensor, are in agreement with these assessments. However, as the work by Fehlmann et al 15 showed, the operating principle of the laser disdrometer, relying on hydrometeor mass density estimations, will result in uncertainties when transforming the raw data to a precipitation rate in the case of falling snow. Therefore, it is difficult to assess if our observed large variations in transmission with respect to precipitation rate is due to inherent variations in the precipitation, or variations introduced by the measurement equipment, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fehlmann et al evaluated a Thies laser disdrometer similar to the one used in the reported campaign with respect to monitoring rain and snowfall events. 15 In the experiments, they compared the results from the laser disdrometer with the results from a pluviometer from OTT and a 2DVD video disdrometer from Joanneum research. The pluviometer was used as a reference for precipitation rate and the 2DVD disdrometer was the reference for PSD measurements.…”
Section: Experimental Setup and Signal Processingmentioning
confidence: 99%
See 1 more Smart Citation